APPLICATION OF STATISTICAL ANALYSIS FOR MEDICAL DATA - Дорошенко, Ірина; Кнігніцька, Тетяна (Modern engineering and innovative technologies, 2024)
The article explores the application of diverse statistical approaches and machine learning methods in medicine. A model analysis was conducted using patient data, where factors influencing the likelihood of stroke occurrence were identified. Data analysi